FEATURES OF COURSE OF PREGNANCY AND DELIVERY IN HIV-INFECTED WOMEN WITH A PREMATURE BIRTH - Ольга Александровна Яковлева; Елена Николаевна Кравченко; Лариса Владимировна Куклина; Ярослав Владимирович Тихоненко (The Publishing House Medicine and Enlightenment, 2018)
The aim of the research - identify features of the course of pregnancy, childbirth and the postpartum period in HIV-infected women with preterm labor. Materials and methods. A retrospective study was conducted, which included 87 pregnant HIV-positive women with preterm birth for the period 2008-2016, which was 43.2 % of all deliveries in HIV-positive women. The epidemiological, clinical and anamnestic data, the characteristics of the course of pregnancy, childbirth and the postpartum period, methods of delivery and the state of newborns were assessed. Results. The average age of the patients was 27 ± 5.2 years. The diagnosis of HIV infection was established before pregnancy in 53.2 %, during pregnancy - in 46.8 % (in the first trimester - in 12.8 %, in II - in 27.6 %, in III - in 6.4 %). In the first trimester antiretroviral therapy was started in 48.9 % of pregnant women, in II - in 36.2 %, in III - in 6.4 %, 8.5 % of patients did not perform chemoprophylaxis during pregnancy. The course of pregnancy was complicated by the threat of termination of pregnancy in 27.7 % of patients, placental insufficiency with fetal retardation - in 38.3 %, gestational edema - in 14.9 %, toxic hepatitis - in 27.7 %, polyhydramnios - in 4.3 %, anhydrite - in 6.4 %, thrombocytopenia - in 8.5 %. Very early premature births accounted for 7 %, early - 68 %, late premature birth - 25 %. 35 % of infants had a delay in fetal development of 1-2 degrees, 87 % had a diagnosis of cerebral ischemia of 1-2 degrees, but respiratory failure was observed only in 15 % of cases. Conclusion. The percentage of preterm delivery in HIV-infected patients is much higher than in the population. HIV infection is a risk factor for premature delivery. Among complications of pregnancy in HIV-infected women, there is often a threat of interruption, placental insufficiency, delayed fetal growth. Among the pathologies of newborns, delayed fetal development and central nervous system damage were leading.